A phase-field model for creep behavior in nickel-base single-crystal superalloy: Coupled with creep damage. (1st April 2018) - Yang, Min; Zhang, Jun; Wei, Hua; Gui, Weimin; Su, Haijun; Jin, Tao; Liu, Lin
Abstract: This paper focuses on the simulation of microstructural evolution during the three stages of creep in nickel-base single-crystal superalloys. A phase-field model coupled with a single-crystal plasticity model is developed in this paper. The creep damage and γ′-shearing during tertiary creep are considered in the phase-field model for the first time. The complete evolutions of γ′/γ phases during all three stages of creep are primarily simulated, and the simulated creep curve shows typical three creep deformation stages. The distribution of plastic strain is illustrated to analyze the morphological evolution and creep mechanism. Graphical abstract: Image 1